Discrimination of Streptococcus equi subsp. equi and Streptococcus equi subsp. zooepidemicus using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. (September 2017) - Mani, Rinosh J.; Thachil, Anil J.; Ramachandran, Akhilesh
Accurate and timely identification of infectious etiologies is of great significance in veterinary microbiology, especially for critical diseases such as strangles, a highly contagious disease of horses caused by Streptococcus equi subsp. equi . We evaluated a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) platform for use in species- and subspecies-level identification of S. equi isolates from horses and compared it with an automated biochemical system. We used 25 clinical isolates each of S. equi subsp. equi and S. equi subsp. zooepidemicus. Using the MALDI-TOF MS platform, it was possible to correctly identify all 50 isolates to the species level. Unique mass peaks were identified in the bacterial peptide mass spectra generated by MALDI-TOF MS, which can be used for accurate subspecies-level identification of S. equi . Mass peaks (mass/charge, m / z ) 6, 751.9 ± 1.4 (mean ± standard deviation) and 5, 958.1 ± 1.3 were found to be unique to S. equi subsp. equi and S. equi subsp. zooepidemicus, respectively. The automated biochemical system correctly identified 47 of 50 of the isolates to the species level as S. equi, whereas at the subspecies level, 24 of 25 S. equi subsp. equi isolates and 22 of 25 S. equi subsp. zooepidemicus isolates were correctly identified. Our results indicate that MALDI-TOF MS can be used for accurate species- and subspecies-level identification of S. equi .